Effectiveness of Pre-Sowing Treatments on Seed Germination of Nine Acacia Species from Al-Baha Region in Saudi Arabia - Ali A. Alzandi; Ibrahim M. Aref; Nels Grevstad (Seeds, 2025)
Acacia species are important trees in arid ecosystems due to their diverse ecological roles, such as providing vegetation cover, community structures, food resources for animals, soil stabilization, and erosion prevention. However, in the Arabian Peninsula, Acacia species are declining due to climate change, overgrazing, and fuelwood harvesting. This study evaluates the effectiveness of various pre-sowing treatments—sulfuric acid soaking and tap and hot water soaking—on breaking seed dormancy to enhance germination in nine Acacia species native to the Al-Baha region of Saudi Arabia. The key germination indicators assessed were the mean germination time (MGT), germination percentage (GP), and germination index (GI). Sulfuric acid treatments for 10–15 min reduced the MGT and increased the GP for A. etbaica, A. hamoulosa, and A. tortilis, while A. origena responded best to 1 min of hot water soaking. Conversely, A. asak, A. ehrenbergiana, and A. johnwoodii showed little to no germination improvement with treatment and A. oerfota and A. gerrardii showed no germination improvement, indicating the need for alternative methods. These findings indicate that the seed germination requirements vary within Acacia spp. from the same geographic region and similar climatic conditions. Further work is required for five of the species tested to develop better seed germination techniques, given the potential utility of Acacia spp., in ecological restoration and sustainable land management in arid regions.